Мова і нація - Пашук, А. (Соціогуманітарні проблеми людини, 2010)
У статті з’ясовується принципове питання долі української мови в історії українського народу. Водночас висувається питання захисту української мови як у минулі століття, так в умовах сучасної України. An essential question of fate of the Ukrainian language in the history of the Ukrainian people is found out in the article. At the same time a question of protection of the Ukrainian language is pulled out both in the previous centuries and in the conditions of modern Ukraine.